Ways of Promoting the Print Media in Poland - Mikosz, Joanna (Journal of Applied Cultural Studies, 2016)
The goal of this article is to identify and describe ways of promoting print media, and demonstrate their effectiveness. The geographical scope of the research was the territory of Poland The thesis is an attempt to describe the above factors, all of which have an impact on the promotion of print media. The thesis is an attempt to describe the above factors, all of which have an impact on the promotion of print media. The main tool used to research the contents of the press was an analysis of non-verbal content and an attempt to determine the proportions between them.